The Drivers of Vulnerability to Climate Change for Banana Growers in Tanzania: University of Dar es Salaam - selejio, Onesmo; Mrema, Hildo (Tanzania Journal for Population studies and Development, 2025)
Bananas are a key staple food and cash crop in Tanzania, supporting millions of smallholder farmers with food security and income. However, its production is increasingly constrained by climate change, pests and diseases, soil degradation, and market fluctuations, which threaten both crop output and household welfare. This study examined the vulnerability of banana growers to climate change, and its key drivers. Using the first three waves (2008/09, 2010/11 and 2012.13) of the Tanzania National Panel Survey data (TNPS), a vulnerability index was constructed through principal component analysis (PCA), while drivers of vulnerability were established using a fixed effects model. The results from the PCA show that 89.34% of banana-growing households are highly vulnerable, primarily due to low adaptive capacity. The average vulnerability index for the entire period covered by this study was -56.28, which is considered high; and is mainly attributed to drought and flood shocks, plot slope, and soil erosion. The fixed effects analysis revealed that household education spending and banana sales value significantly reduce vulnerability. In contrast, higher productivity, rising average temperatures, and year fixed effects were found to exacerbate vulnerability. Based on these findings, key policy options include enhancing access to education, agricultural extension services, and good markets; as well as promoting climate-smart agricultural practices. Such measures are vital for building resilience and securing the sustainably of banana-dependent livelihoods.